The Linguistic Repertoires of Young Learners in Iceland: Multimedia, Subtitles, and Native Language Vocabulary Acquisition - Birkir Már Viðarsson 1992- (2016)
Subtitles have been shown to play a key role in foreign and second language vocabulary acquisition but that poses the question as to whether they play a key role in native language vocabulary acquisition. As new forms of media impact Icelandic society and television viewership declines, the presence of Icelandic subtitles in the lives of young learners in Iceland is diminished. Young learners in Iceland are becoming more proficient in the English language as a result of the changed linguistic environment in Iceland, especially due to the arrival of new forms of media. The research question of this study is whether young learners in Iceland incidentally learn Icelandic vocabulary from watching audiovisual material in English with Icelandic subtitles. A group of young learners in their tenth year were asked to answer an Icelandic vocabulary definition task before and after they were exposed to an episode of The Simpsons with Icelandic subtitles. Despite the fact that the numerous limitation of the study detract from the significance of the results, the results of the study support the notion that children incidentally learn Icelandic vocabulary from watching audiovisual material in English with Icelandic subtitles.